CONTRASTIVE ANALYSIS OF INTRANSITIVE VERBS USE IN SUNDANESE AND ENGLISH - Rizky Agung Fardani; Yanuarius Yanu Dharmawan (Universitas Bandar Lampung, 2017)
The purpose of this research is to know how intransitive verbs in Sundanese and English have their own characteristics. The technique used in this research is contrastive. In other words, this research technique focuses on the differences and equations that exist in both languages. This method has also been used by several researchers and considered as research methods that are relevant enough to find differences and similarities to the object to be studied.In this study, I used the qualitative description method. This method is used to experience real-world experience, and also to know people's point of view in a certain phenomenon. It is also used to get the correct, systematic and well-structured explanation. This research is conducted referring to Sundanese language as one of indigenous language in Indonesia. Then, my Sundanese language contrasts by referring to English as a foreign language by looking at some of the famous dictionaries. To collect the data, I made observations and analyzes on each verb. This data is analyzed by looking at some of the dictionaries that I use as the main reference.The results of this study indicate that when I first did this there were many difficulties in collecting data. Then, from the results of my research over the course of a few weeks, I have collected 8 commonly used verbs and taken into the research section.From what I have done, it has been seen that this study shows the differences in sentence structure of both languages. However, there are similarities found that in the context of the meanings of each verb does not have any change in the two languages.